Evaluation of posterior vitreous detachment after uneventful phacoemulsification surgery by optical coherence tomography and ultrasonography. (20th July 2016) - Degirmenci, Cumali; Afrashi, Filiz; Mentes, Jale; Oztas, Zafer; Nalcaci, Serhad; Akkin, Cezmi
Abstract: Background: The aim was to investigate the effect of uneventful phacoemulsification on vitreoretinal interface evaluated by optical coherence tomography (OCT) and ultrasound. Methods: One hundred and fifty eyes were evaluated for the presence or absence of posterior vitreous detachment by ultrasound and OCT prior to cataract surgery. Only those eyes with intact vitreoretinal adhesion were included in the study. All patients underwent cataract surgery. At one month, three months and six months, all patients were assessed with OCT and ultrasound. The data were analysed for statistical significance. Results: The study was carried out on 30 of 31 patients with no posterior vitreous detachment. The mean age of patients was 62.63 ± 7.15 years (range 49 to 75 years) and 15 were female. Posterior vitreous detachment developed in 17 patients (56.66 per cent) at one month, 21 patients (70 per cent) at three months and 22 patients (73.33 per cent) at six months following the surgery. No complications or acute symptoms were detected associated with posterior vitreous detachment. Conclusion: Vitreoretinal interface changes and vitreoretinal separations and progression of separation can be easily evaluated by OCT. The current study confirms that posterior vitreous detachment occurs commonly soon after cataract surgery.